What is the solution of the equation (x – 5)2 + 3(x - 5) + 9 = 0? Use u substitution and the quadratic formula to solve.
A. x. -3 plus or minus 3i square root of 3 over 2
B. X= 7 +or- 3i square root of 3 over 2
C. x = 2
D. x=8

Respuesta :

Answer:

  B

Step-by-step explanation:

Let u = (x-5). Now the equation becomes a quadratic in u:

  u² +3u +9 = 0

Using the quadratic formula, we have a=1, b=3, c=9 and ...

  [tex]u=\dfrac{-b\mp\sqrt{b^2-4ac}}{2a}=\dfrac{-3\pm\sqrt{3^2-4(1)(9)}}{2(1)}=\dfrac{-3\pm\sqrt{-27}}{2}\\\\x-5=\dfrac{-3\pm3i\sqrt{3}}{2}\qquad\text{substitute for u}\\\\\boxed{x=\dfrac{7\pm3i\sqrt{3}}{2}}\qquad\text{add 5; matches choice B}[/tex]